Teaching Technology:: Skins vs. Structures - Meyer Boake, Terri (ARCC Conference Repository, 2019)
Technological developments over the last hundred years have resulted in the compounding of materials issues as they relate to architectural design. Structural steel and concrete systems, as well as different varieties of load bearing masonry design have radically altered the structural design processes for buildings. The changeover from the predominant use of load bearing exterior walls to curtain walls and rainscreen elements, has also complicated issues related to the design of exterior wall systems. Environmental awareness has been introduced to the equation and has required significant changes to envelope design as relates to climate and energy issues.